YOUTH EMPLOYMENT IN SOMALIA: NAVIGATING THE CHALLENGES OF GRADUATE UNEMPLOYMENT - Abukar, Mohamed Ahmed; Hassan, Fatima Abdi; Mohamed, Abdirahman Ali (International Journal of Allied Research in Economics (IJARE), 2023)
Graduate unemployment is a serious problem in many countries, and Somalia is no exception. The country has an estimated youth unemployment rate of over 70%, which is one of the highest in the world. This problem has a number of negative consequences, including poverty, crime, and social unrest. The causes of graduate unemployment in Somalia are complex and include factors such as the lack of a strong economy, the poor quality of education, and the lack of opportunities for young people. There are a number of potential solutions to this problem, including increasing investment in education and job creation, and providing training and skills development programs for young people